CIRSOID ANEURYSM - Mohammad, Gul; Mufti, Tariq (Journal of Ayub Medical College Abbottabad, 1991)
25 years old male admitted with a painful, generalised swelling over the right Fronto-ParietoTemporal region of scalp. He had a recent history of bleeding from different points of swelling off and on. There was a central pulsatile and bald area of 6x9 cm with collapsible subcutaneous vessels. Bruit was heard over this area. A diagnosis of cirsoid aneurysm was made. X-ray of the skull showed erosion of underlying calvarium. The swelling was dealt with in two stages. Initially a unilateral superficial temporal vessel ligation was carried out along with ligation of some of the pulsatile veins which were considered to be communicating intracranally. In second stage after an interval of 3 months the central area of the cirsoid was excised along with the ligature of other branches of the superficial temporal vessels. The scalp was mobilised all over the aneurysmal area and the dilated veins were carefully secured and rotation flap was made to cover the skin defect. Patient made excellent recovery and wound healing. Patient was reviewed after 6 months at which time he was recurrence free.